Kaika69
Rozwiązane

2. Uprość wyrażenie.
a) (3x + 4) - X(2 + 9x)
b) 2p(3-8p) + (1 + 4p)
c) (5a - b) + b(10a - b)
d) y(4x + y) - (x + 2y)
e) (3m - 2)+ (6m + 13
d) (5a + b)2-(b-5a)-



Odpowiedź :

Odpowiedź:

[tex]a) (3x + 4) - x(2 + 9x) = 3x + 4 - 2x - 9x^{2} = x + 4 - 9x^{2}[/tex]

b) [tex]2p(3 - 8p) + (1 + 4p) = 6p - 16p^{2} + 1 + 4p = 10p + 1 - 16p^{2}[/tex]

c) [tex](5a - b) + b(10a - b) = 5a -b +10ab - b^{2}[/tex]

d) [tex]y(4x + y) - (x + 2y) = 4xy + y^{2} - x - 2y[/tex]

e) [tex](3m - 2) + (6m + 13) = 3m - 2 + 6m + 13 = 9m - 11[/tex]

f) [tex](5a + b)2 - (b - 5a) = 10a + 2b - b - 5a = 5a + b[/tex]

Inne Pytanie